2021
DOI: 10.1111/kykl.12262
|View full text |Cite
|
Sign up to set email alerts
|

Does economic freedom boost growth for everyone?

Abstract: While the association between economic freedom and long‐term economic growth has been well documented, the parallel research literature on the distributional consequences of economic freedom is full of conflicting findings. In this paper, we take a step toward reconciling these two bodies of literature by exploring the within‐quintile growth consequences of changes in three separate elements of economic freedom: the size of government, institutional quality and and policy quality. Although the distributional c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 88 publications
0
12
0
Order By: Relevance
“…One dimension of institutional quality is the degree of economic freedom. Recently, it has been showed that economic freedom not only raises productivity on average but does so for all income classes and thus is desirable also from a perspective of equality (Bergh & Bjørnskov, 2021, p. 183). More closely related to our issue of citizenship are, for example, Shachar (2009, pp.…”
Section: The Citizenship As Propertymentioning
confidence: 99%
“…One dimension of institutional quality is the degree of economic freedom. Recently, it has been showed that economic freedom not only raises productivity on average but does so for all income classes and thus is desirable also from a perspective of equality (Bergh & Bjørnskov, 2021, p. 183). More closely related to our issue of citizenship are, for example, Shachar (2009, pp.…”
Section: The Citizenship As Propertymentioning
confidence: 99%
“…For example, Berggren (1999) showed that EF lessens inequality in 66 countries in the period 1975–1985 by increasing the income share of held by the lowest quintile, and reducing that by the highest one. Although the growth effects are largest for the poorest and richest quintiles, EF affects all parts of the income distribution equally (Bergh and Bjornskov, 2021). Likewise, Scully (2002) found a beneficial effect of EF on income equality and economic growth, and there is a small trade‐off between growth and income inequality for a sample of 26 developed countries over the period 1975–1990.…”
Section: Literature Reviewmentioning
confidence: 99%
“…One detailed study (Compton et al, 2014) looking solely at the impact of increasing economic freedom on income growth across American quintiles between 1981 and 2004 confirmed that the majority of people indeed benefited but warned that the positive effect was strongest at the top (see also Ashby and Sobel, 2008). Another recent study employing global data for the period between 1975 and 2015 finds that, holding all else constant, increases in economic freedom resulted in no differences in income growth across all five quintiles (Bergh and Bjørnskov, 2021). As the authors put it, ‘our findings clearly suggest that the consequences of reforms that increase economic freedom will boost medium-run growth for all five income quintiles.…”
Section: Measuring Neoliberalism’s Impact Through Indexes Of Economic...mentioning
confidence: 99%